Changes in Land Distribution of Polar Bears in Western Hudson Bay - Towns, Lindsay; Derocher, Andrew E.; Stirling, Ian; Lunn, Nick J. (ARCTIC, 2010)
We examined the capture locations of polar bears (Ursus maritimus) on land in western Hudson Bay over 19 years (1986–2004) to assess temporal trends in the distribution of the population. We found that the distribution of bears of most age and sex groups shifted northward and eastward over the study. The causes of these shifts may be related to an altered population structure, changing environmental conditions, or a combination of both factors. Segregation by age, sex, and reproductive status persisted over time as found in earlier studies, but more females with young were within 5 km of the coast after 2001 than before. The distribution changes were correlated with the timing of sea-ice breakup, which now occurs, on average, about three weeks earlier than it did 30 years ago. While environmental conditions may have influenced polar bear distribution, the reduction in the number of large adult males along the coast may also have affected distribution patterns, allowing adult females to remain closer to the coast in more recent times. Nous avons examiné les lieux de capture d’ours polaires (Ursus maritimus) sur la terre ferme dans l’ouest de la baie d’Hudson pendant 19 ans (de 1986 à 2004) afin d’évaluer les tendances temporelles caractérisant la répartition de la population. Nous avons remarqué que la répartition des ours de la plupart des groupes d’âge et de sexe se déplaçait vers le nord et vers l’est au cours de l’étude. Cela pourrait être attribuable à une structure de population modifiée, à l’évolution des conditions environnementales ou à un ensemble des deux facteurs. La ségrégation en fonction de l’âge, du sexe et de l’état reproducteur a persisté avec le temps, tel que dénoté dans le cadre d’études antérieures, mais plus de femelles avec des jeunes se trouvaient en-dedans de cinq kilomètres de la côte après 2001 qu’avant. Les changements en matière de répartition ont été corrélés au moment de la débâcle de la glace de mer qui maintenant se produit, en moyenne, environ trois semaines plus tôt qu’il y a ...